Effects of oral N-acetyl cysteine on pain and plasma biochemical parameters in fibrocystic breast disorder: A randomized controlled trial - Esmail Abdorrahim Kashi, MD; Ali Akbar Salmani, MD; Shima Shafagh, MD; Gholam Abbas Mousavi, PhD; Noushin Mousavi, MD; Mahmoud Heydari, MD; Abbas Hajian, MD (Surgery Open Science, 2022)
Background: Fibrocystic change is the most common benign lesion in breasts of a woman in her reproductive age. It is an outcome of estrogen excess due to sex hormone imbalance. Cyclical pain as the most common symptom worsens life quality, compels patient to seek health care support continuously, and imposes large amounts of expense to both patient and health system. Current study aims to evaluate effects of N-acetyl cysteine on decreasing pain and changes in plasma biochemistry. Method: A total of 64 eligible women participated in this double-blinded randomized controlled trial. They were between 18 and 40 years. Participants were randomly allocated into oral N-acetyl cysteine and placebo receivers. Intervention and follow-up lasted for, respectively, a 12-week drugs-on and 12-month drugs-off period. Visual analog scaling was applied to measure severity of pain. Peripheral venous plasma was extracted and compared for inflammatory parameters including high-sensitivity C-reactive protein, total antioxidant capacity, malondialdehyde, total plasma glutathione, lipid profile, and fasting blood sugar. Results: Oral N-acetyl cysteine significantly decreased feeling of cyclical mastalgia (P < .01) after 12 weeks of consumption. In addition to lowering of plasma level of high-sensitivity C-reactive protein (P = .008), total plasma glutathione significantly increased (P = .02) among N-acetyl cysteine receivers. No change in lipid profile and insulin sensitivity was seen. Conclusion: N-Acetyl cysteine could mitigate cyclical mastalgia. Inflammation as a considered reason for cyclical mastalgia also was halted by N-acetyl cysteine consumption.